Methodological quality of systematic reviews comprising clinical practice guidelines for cardiovascular risk assessment and management for noncardiac surgery. (December 2021) - Jacobsen, Samuel M.; Douglas, Alexander; Smith, Caleb A.; Roberts, Will; Ottwell, Ryan; Oglesby, Benson; Yasler, Coy; Torgerson, Trevor; Hartwell, Micah; Vassar, Matt
Abstract: Background: Cardiac assessment in noncardiac surgery clinical practice guidelines should be supported by the highest-quality evidence such as that offered by systematic reviews. Currently, the methodological and reporting quality of these studies remains unknown. Methods: We used PubMed to search for all clinical practice guidelines related to perioperative cardiovascular patients undergoing noncardiac surgery from 2010 to 2021. The included clinical practice guidelines were analysed for all systematic reviews and meta-analyses. The primary objective of this study was to determine reporting and methodological quality using the PRISMA (Preferred Reporting Instrument for Systematic Reviews and Meta-Analyses) and AMSTAR-2 (A Measurement Tool to Assess Systematic Reviews-2) instruments. Our secondary objective was to compare systematic reviews conducted by the Cochrane Collaboration with non-Cochrane studies. Results: Three clinical practice guidelines were included in our study. Within these, 78 systematic reviews were included. PRISMA completion ranged from 34.8% to 100.0% with a mean of 76.9%. AMSTAR-2 completion ranged from 15.6% to 96.9% with a mean of 58.0%. Fifty-four systematic reviews underpinned a clinical practice guidelines recommendation, of which 25 were rated 'critically low' by AMSTAR-2 appraisal. Cochrane systematic reviews typically performed better than non-Cochrane studies, but were a minority of the included studies (10/78). Conclusion: We found deficiencies in several key areas regarding the methodological and reporting qualities of systematic reviews included in cardiac assessment in noncardiac surgery clinical practice guidelines. As these clinical practice guidelines are instrumental to clinical decision-making and patient care in cardiac assessment in noncardiac surgery, we advocate for improved reporting quality among systematic reviews cited as supportive evidence for these recommendations.